Functions of IFNλs in Anti-Bacterial Immunity at Mucosal Barriers - Alphonse, Noémie; Dickenson, Ruth E.; Alrehaili, Abrar; Odendall, Charlotte (Frontiers in Immunology, 2022)
Type III interferons (IFNs), or IFNλs, are cytokines produced in response to microbial ligands. They signal through the IFNλ receptor complex (IFNLR), which is located on epithelial cells and select immune cells at barrier sites. As well as being induced during bacterial or viral infection, type III IFNs are produced in response to the microbiota in the lung and intestinal epithelium where they cultivate a resting antiviral state. While the multiple anti-viral activities of IFNλs have been extensively studied, their roles in immunity against bacteria are only recently emerging. Type III IFNs increase epithelial barrier integrity and protect from infection in the intestine but were shown to increase susceptibility to bacterial superinfections in the respiratory tract. Therefore, the effects of IFNλ can be beneficial or detrimental to the host during bacterial infections, depending on timing and biological contexts. This duality will affect the potential benefits of IFNλs as therapeutic agents. In this review, we summarize the current knowledge on IFNλ induction and signaling, as well as their roles at different barrier sites in the context of anti-bacterial immunity.